TNF receptor-associated factors: promising targets of natural products for the treatment of osteoporosis - Yang, Xicheng; Zhao, LiLi; Pang, YinQuan (Frontiers in Physiology, 2025)
Tumor necrosis factor receptor-associated factors (TRAFs) are crucial intracellular signaling proteins in bone homeostasis. TRAFs mediate pathways associated with bone remodeling, particularly in response to inflammatory stimuli, influencing osteoclast differentiation and function. Dysregulation of TRAF-mediated signaling contributes significantly to osteoporosis, a condition marked by increased bone resorption and fragility. Natural products, with their anti-inflammatory and antioxidant properties, offer promising therapeutic potential by targeting TRAF-associated pathways to inhibit excessive osteoclast activity and promote bone formation. This review explores the mechanisms by which natural compounds modulate TRAF signaling in osteoclastogenesis and osteoblastogenesis, providing insights into their potential for osteoporosis treatment.